Understanding Developmental Perspective of Writing as a Framework for Early Grades Writing Pedagogy - Kunwar, Nidhi (JOURNAL OF INDIAN EDUCATION, 2023)
Developmental perspective is a significant framework for early-grade pedagogy. It believes in the agency of young children and highlights their active role in learning writing. The present paper is focused on the developmental perspective of writing. The paper discusses the underlying theoretical framework of developmental perspective and offers educational implications specifically for early-grade writing pedagogy. It also highlights the contrast between the core ideas of developmental perspective and writing pedagogy popularly practiced in our classrooms.